2006
DOI: 10.1105/tpc.106.043299
|View full text |Cite
|
Sign up to set email alerts
|

CONSTANS and the CCAAT Box Binding Complex Share a Functionally Important Domain and Interact to Regulate Flowering ofArabidopsis

Abstract: The CCT (for CONSTANS, CONSTANS-LIKE, TOC1) domain is found in 45 Arabidopsis thaliana proteins involved in processes such as photoperiodic flowering, light signaling, and regulation of circadian rhythms. We show that this domain exhibits similarities to yeast HEME ACTIVATOR PROTEIN2 (HAP2), which is a subunit of the HAP2/HAP3/HAP5 trimeric complex that binds to CCAAT boxes in eukaryotic promoters. Moreover, we demonstrate that CONSTANS (CO), which promotes Arabidopsis flowering, interacts with At HAP3 and At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
576
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 557 publications
(596 citation statements)
references
References 72 publications
(100 reference statements)
16
576
1
3
Order By: Relevance
“…6 Among other things, HAP factors are known to be involved in the regulation of flowering and to bind to CCAAT box motifs in the promoter region of their target genes. 18 Two such CCAAT boxes can be found in the AMI1 promoter, 266 and 462 bp upstream of the start codon, respectively. Our hypothesis is further supported by the expression pattern of the corresponding genes as can be taken from publicly available databases (www.genevestigator.com/gv/index.jsp).…”
Section: Ami1 Expression Is Presumably Suppressed By Lec1mentioning
confidence: 99%
“…6 Among other things, HAP factors are known to be involved in the regulation of flowering and to bind to CCAAT box motifs in the promoter region of their target genes. 18 Two such CCAAT boxes can be found in the AMI1 promoter, 266 and 462 bp upstream of the start codon, respectively. Our hypothesis is further supported by the expression pattern of the corresponding genes as can be taken from publicly available databases (www.genevestigator.com/gv/index.jsp).…”
Section: Ami1 Expression Is Presumably Suppressed By Lec1mentioning
confidence: 99%
“…It has been suggested that photoperiod-dependent flowering involves nuclear factor Y (NF-Y) complexes, which are conserved combinatorial transcription factors in eukaryotes consisting of NF-YA, NF-YB and NF-YC subunits [28][29][30][31][32] . NF-Y and its binding element, the CCAAT box, are among the first set of trans-acting factors and cis-elements identified in eukaryotes 33 .…”
mentioning
confidence: 99%
“…In addition, recent systematic studies in Arabidopsis have revealed that physical interaction between AtNF-YB and AtNF-YC is required for the formation of the entire heterotrimeric complex, prior to binding to the consensus CCAAT motif, as shown for mammalian cells Hackenberg et al 2012). The AtNF-YC3, AtNF-YC4, and AtNF-YC9 proteins are also known to interact with the AtNF-YB2, AtNF-YB3, and CO subunits (Kumimoto et al 2010), suggesting that the AtNF-YC subunits make heterotrimeric complexes with AtNF-YB2 or AtNF-YB3 and CO to provide unique platforms for the finetuning of flowering under various environmental conditions (Wenkel et al 2006;Kumimoto et al 2010). Contrary to the canonical NF-Y complexes, CO/AtNF-YB/AtNF-YC trimeric complexes are speculated not to bind the CCAAT motif in the FT promoter, because the CO protein does not have the essential histidine residues required for NF-Y complex binding 6 (Xing et al 1993;Siefers et al 2009;Kumimoto et al 2010).…”
Section: Introductionmentioning
confidence: 92%
“…CO protein is known to interact with AtNF-YC3, 4 and 9 proteins via the CCT domain (Wenkel et al 2006;Kumimoto et al 2010). In wheat, VRN2 [acting as a flowering repressor (Yan et al 2004)] and CO2 [acting as a flowering promoter (Nemoto et al 2003)] also physically interact with the same subset of eight TaNF-Y proteins .…”
Section: Possible Interactions Between Osnf-yb or Osnf-yc Proteins Amentioning
confidence: 99%
See 1 more Smart Citation